Understanding unidentified human remains investigations through the United States census data - Ashley L. Rodriguez; Hope M. Smiley-McDonald; M. Stirling Cummings; Sean Wire; Donia Slack; Christopher L. Williams; Kelly A. Keyes; Jeri D. Ropero-Miller (Forensic Science International: Synergy, 2022)
Each year, thousands of unidentified human remains (UHR) cases are reported in the U.S. Technological advances have greatly enhanced the forensic community's capacity and capability to solve UHR cases, but little is known about the extent to which these resources are used by medical examiners and coroners (MECs). Using public datasets, the study purpose is to describe the current state MEC system with respect to UHR cases, the resources used to investigate these cases, and the evidence retention polices in place. There was an overall decline in UHR cases reported between 2004 and 2018. Less than half of MECs in both study years reported having established written final disposition and evidence retention policies for UHR cases. National missing persons databases were underused. This study provides an important window into the present state of UHRs being handled by our Nation's MEC offices and the resources available to solve these difficult cases.